RARE MINERALS IN GRĂDIŞTEA DE MUNTE AREA,ŞURIANU MOUNTAINS, ROMANIA (PANGEEA, 2025)
Mineralogical features of the minerals of Gradiştea de Munte demonstrate its long multistage crystallization. The multi-staged mineralizing process is supported by textural relationships of all rare mineral constituents of ore, where replacement of earlier minerals by later ones is common. The textural relations between Nb, REE(Y), Th, U and Zr minerals, and between the zircon and minerals of the host rock, show that zircon/cyrtolite shows many generations: the old zircon occurs as discrete grains in phlogopite and magnetite, is well crystallized, transparent, similar to igneous zircon; the zircon/cyrtolite have a texture consisting of a mixture of two microdomains, metamict and crystalline. The new zircon generations overgrown as small clean crystals, as a fringe on cyrtolite, baddeleyite, thorite, etc could be considered as resulting from hydrothermal processes. Their geochemical zoning indicates a different origin of each part of the crystal. Representative microprobe analysis of Grădiştea de Munte zircon/cyrtolite show high contents of Th, Y, Yb, Ce, Hf; U and less La, Nd, Sm, Dy and Nb. The heavy rare earth elements (HREE), especially Y, beside Th and sometimes Hf; are the predominant trace elements in zircon/cyrtolite, because of their similarity in ionic radius to Zr4+. The baddeleyite occurrence as one of the oldest mineral, indicates that the first vein mineralizing solutions were subsaturated in silica. The absence of silica has stabilized baddeleyite and its presence has stabilized zircon/cyrtolite.
Keywords: zircon; cyrtolite; yttropyrochlore; uranpyrochlore; thorite; cassiterite; baddeleyite